Differentiated reading instructional materials for grade four - Abellar, Fe Abunda
This study consists of instructional materials that cater to the needs of at least three different reading levels within a grade. The stories and selections which have been graded with the use of the Dale-Chall Readability Formula and the opinion of "experts" were taken from supplementary readers used in the field and from the Reader's Digest Skill Builders, some were adapted, others taken in original form.